Tax Goes to Campus as an Effort to Include Tax Awareness at LP3I Tasikmalaya Polytechnic - Usmar, Andi; Sofyan, Harnavela; Surayuda, Rama Nugraha Irawan; Munggaran, Rangga; Sofyan, Verra Rosyalia Widia; Fitriani, Rani Ligar; Sanjayyana, Adzka Rosa; Bahiyyah, Khariidatul; Kurniawati, Yuyun; Romdoni, Nijar Kurnia; Sutarsa, Monika (PT. Riset Press International, 2025)
This activity explores the implementation of the